Promising indicators for effectively targeting the poor in Myanmar - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
The social protection system in Myanmar has remained at a rudimentary level for the past decade, with policies scattered and fragmented across various government departments, and serving only a fraction of the eligible population. The government allocated only 0.8 percent of its expenditure to social protection constraining its ability to expand to vulnerable groups leaving households to rely on informal forms of safety nets against idiosyncratic and covariate shocks, and life-course contingencies (Niño-Zarazúa & Tarp 2021). Only 13.8 percent of the population received any form of social protection according to the 2017 MLCS, leaving much of the poor, which is about one-third of the population, out of the scope of protection. After the military takeover in 2021, government provision of social protection faced a complete collapse with near zero allocation to the population (MAPSA 2022c). In the face of the double predicament of the COVID-19 pandemic and coup, any form of anti-poverty investment should effectively target the poor based on observable and verifiable characteristics. In this research note, we explore some promising indicators which can be used by implementing agencies to effectively target the poor. We use data from the Myanmar Household Welfare Survey (MHWS) collected over the phone during July and August of 2022. The survey was conducted among 12,000 households in 310 townships of Myanmar. The MHWS is a nationally, urban/rural and state/region representative phone survey (MAPSA 2022a). The household survey questionnaire collected information on a wide variety of topics such as household composition, occupation, education, dwelling characteristics, assets, income, and agriculture.